Towards a more realistic view on the market potential of EU securitizations - Frank Brückbauer; Karolin Kirschenmann (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Ongoing global trends like climate change require firms to invest in projects that support their transformation. In order to unlock the huge sums of private capital necessary for these investments, the engagement of institutional investors appears to be crucial. In a project funded by ZEW's Sponsors' Association, we investigate whether and how a better integration of the European banking system and capital markets can be an effective short- and medium-term solution to unleash the financial sector's potential in supporting the green transformation. Capital markets can support bank lending by financing assets on- and off-balance-sheet. Securitizations allow institutional investors to directly invest into cash flows from specific assets. Our analysis shows that the current market potential of European securitizations is much smaller than wished for and that the securitization model envisaged by the Capital Markets Union (CMU) project does not seem to fit the European context. Instead, policymakers should embrace a realistic view on the market potential of European securitizations. They also need to be clear in their communication about the trade-offs between unconventional central bank policies and the development of securitization markets. Additionally, they should closely watch the incentives that come with the new non-financial reporting indicators for banks regarding securitization. Most importantly, to accelerate the green transition, policymakers need to encourage the necessary private real investments in the first place by creating a conducive economic environment and the right incentives.
Keywords: 330